Risk of Developmental Coordination Disorder in Italian very preterm children at school age compared to general population controls. (March 2019) - Caravale, Barbara; Herich, Lena; Zoia, Stefania; Capone, Luca; Voller, Fabio; Carrozzi, Marco; Chiandotto, Valeria; Balottin, Umberto; Lacchei, Maria; Croci, Ileana; Cuttini, Marina
Abstract: Background: Developmental Coordination Disorder (DCD) is a neurodevelopmental disorder that involves difficulties in goal-directed motor coordination, with ineffective control of fine and gross motor movements in the absence of sensory impairment or neurological condition. DCD is frequently reported in children born very preterm (VP) who survive without CP. Aims: To measure the risk of DCD at school age in a large area-based cohort of VP children and general population controls, adjusting for gender, birth weight by gestational age and age at assessment. Methods: VP children (N = 608) were part of a prospective cohort study in Italy. Controls (N = 370) were participants in the DCDQ-Italian validation study in the same age range. The Italian version of Developmental Coordination Disorder Questionnaire (DCDQ-Italian) was used to measure the performances in motor coordination during ordinary activities from the parental point of view. Multivariable regression analysis was used to obtain adjusted risk ratios of screening positive for DCD. Results: VP children had scores significantly lower than peers, and about 30% of them appeared at risk of DCD using the 15th percentile cut-off of the Italian validation study. Birth-weight <10th percentile for gestational age and male gender were significant predictors. A slight trend effect was present, with extremely preterm children (<28 weeks gestation) showing the highest risk. Conclusions: Our study confirmed the higher DCD risk in VP children, particularly when males and SGA.